Impact of climate change on mental health among vulnerable groups: A systematic literature review - Adi Fahrudin; Wanda Kiyah George Albert; Mari Esterilita; Uut Hanafi Rochman; Nazera Nur Utami; Siti Hajar Abdul Rauf; Azlini Chik; Laila Meiliyandrie Indah Wardani (The global goals, 2024)
Objective: This study aims to explore the impact of climate change on mental health among vulnerable groups, including low-income populations, Indigenous communities, children, women, and the elderly, to highlight their unique vulnerabilities and mental health outcomes. This aligns with the United Nations' Sustainable Development Goals (SDGs), particularly SDG 3 (Good Health and Well-being) and SDG 13 (Climate Action), addressing the need for climate resilience and mental health equity. Theoretical Framework: The research is grounded in social vulnerability theory, emphasizing how structural inequalities exacerbate the impact of climate change on mental health. The framework integrates psychological theories of eco-anxiety and solastalgia, which explain the mental distress caused by environmental changes. Method: A systematic literature review was conducted using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) methodology. This involved a comprehensive search of academic databases, screening studies, and qualitatively synthesizing data from 35 peer-reviewed articles published between 2000 and 2023. Results and Discussion: Findings reveal that climate change exacerbates mental health issues such as anxiety, depression, and PTSD among vulnerable groups due to their limited adaptive capacity and exposure to climate-related hazards. Vulnerable communities, including Indigenous groups and low-income populations, experience heightened psychological impacts such as eco-anxiety and solastalgia. The results underscore the importance of integrating mental health considerations into climate adaptation policies and developing targeted interventions to enhance resilience among these populations. This study also supports global efforts toward achieving SDG 10 (Reduced Inequalities) and SDG 11 (Sustainable Cities and Communities). Research Implication: The study suggests the need for comprehensive and equitable mental health strategies that prioritize vulnerable groups in climate change adaptation planning. Policymakers must consider social equity and community-based approaches to mitigate the mental health impacts of climate change. Originality/Value: This review uniquely addresses the intersection of climate change and mental health within marginalized populations, emphasizing the need for mental health integration in climate adaptation frameworks. The study highlights the underexplored psychological dimensions of climate change, providing valuable insights for developing inclusive and sustainable adaptation strategies. sustainability